Myofibrillogenesis Regulator-1 in Smooth Muscle Cells Modulates Inflammation Signaling Pathways via Regulating ROCK1 Ubiquitination and Degradation to Impact Aortic Dissection - Yin H; Li X; Lu D; Zhao X; Yang Z; Wang Z; Xu F; Chen Y; Li C (Journal of Inflammation Research)
Hang Yin,1– 5,* Xiaoxing Li,6,* Dazhou Lu,1– 5,* Xin Zhao,7,* Zeyu Yang,1– 5 Zerui Wang,1– 5 Feng Xu,1– 5 Yuguo Chen,1– 5 Chuanbao Li1– 5 1Department of Emergency Medicine, Qilu Hospital of Shandong University, Jinan, People’s Republic of China; 2Shandong Provincial Clinical Research Center for Emergency and Critical Care Medicine, Institute of Emergency and Critical Care Medicine of Shandong University, Chest Pain Center, Qilu Hospital of Shandong University, Jinan, People’s Republic of China; 3Key Laboratory of Emergency and Critical Care Medicine of Shandong Province, Key Laboratory of Cardiopulmonary-Cerebral Resuscitation Research of Shandong Province, Shandong Provincial Engineering Laboratory for Emergency and Critical Care Medicine, Qilu Hospital of Shandong University, Jinan, People’s Republic of China; 4Shandong Key Laboratory: Magnetic Field-Free Medicine & Functional Imaging (MF), Qilu Hospital of Shandong University, Jinan, People’s Republic of China; 5NMPA Key Laboratory for Clinical Research and Evaluation of Innovative Drug, Qilu Hospital of Shandong University, Jinan, People’s Republic of China; 6Department of Geriatrics, Qilu Hospital, Shandong University, Jinan, Shandong, People’s Republic of China; 7Department of Cardiovascular Surgery, Qilu Hospital of Shandong University, Jinan 250012, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuanbao Li; Yuguo Chen, Department of Emergency Medicine, Qilu Hospital of Shandong University, Jinan, People’s Republic of China, Email bao2460@126.com; chen919085@sdu.edu.cnBackground: Aortic dissection (AD) is a life-threatening cardiovascular emergency and currently lacks effective drug treatment. Inflammation is a critical mechanism in the development of AD, and identifying specific molecular targets to regulate inflammation is crucial for stopping its progression. This study aimed to investigate the role of MR-1 and ROCK1 in the regulation of inflammation in AD and their potentialities as therapeutic targets.Methods: Researchers performed protein immunoblotting on aortic wall tissue from 10 patients who underwent aortic arch replacement and 10 patients who underwent coronary artery bypass grafting to examine the expression levels of MR-1, ROCK1, and inflammatory pathways in the aortas. In vitro experiments, human aortic smooth muscle cells were extracted, and an in vitro dissection model was constructed with angiotensin II. siRNA silencing studies were performed to investigate the effects of MR-1 and ROCK1 on the development of AD and their interconnections.Results: Analysis of aortic tissues revealed significantly elevated levels of MR-1 and ROCK1 in AD patients, and meanwhile the inflammatory indexes showed the same trend. Furthermore, it was observed that overexpression of MR-1 and ROCK1 facilitated smooth muscle cell phenotypic transformation and augmented matrix metalloproteinase release in in vitro settings through inflammatory pathway activation. The relationship between MR-1 and ROCK1 was elucidated, too.Conclusion: MR-1 and ROCK1 overexpression is associated with the occurrence and development of AD through inflammation. This study highlights the role of inflammation in AD development and tap the potentiality of using MR-1 and ROCK1 as targets to alleviate AD development. Keywords: MR-1, ROCK1, aortic dissection, inflammation, phenotypic switch